Nitrogen Systemic Signaling: From Symbiotic Nodulation to Root Acquisition - Gautrat, Pierre; Laffont, Carole; Frugier, Florian; Ruffel, Sandrine (Elsevier Ltd, 2021)
Plant nutrient acquisition is tightly regulated by resource availability and metabolic needs, implying the existence of communication between roots and shoots to ensure their integration at the whole-plant level. Here, we focus on systemic signaling pathways controlling nitrogen (N) nutrition, achieved both by the root import of mineral N and, in legume plants, through atmospheric N fixation by symbiotic bacteria inside dedicated root nodules. We explore features conserved between systemic pathways repressing or enhancing symbiotic N fixation and the regulation of mineral N acquisition by roots, as well as their integration with other environmental factors, such as phosphate, light, and CO2 availability.
Keywords: carbon; legume; nitrate transport; nitrogen-fixing symbiotic nodule; root development; systemic signaling; Plant Science